Wet Modal Analyses of Various Length Coaxial Sump Pump Rotors with Acoustic-Solid Coupling - Guangjie Peng; Zhuoran Zhang; Ling Bai (Shock and Vibration)
The dynamic characteristics of the rotor components were determined using a first-order modal model of the rotor components for various sump pump shaft lengths for actual working environments. By employing ANSYS-Workbench software, this paper uses a fluid-solid coupling analysis to calculate the reaction forces of the fluid on the rotor with results, which is then used in dry and wet modal analyses of the rotor parts to calculate the vibration modal characteristics with and without prestresses. The differences between the wet and dry modal characteristics were compared and investigated by ANSYS. The results show that increasing the sump pump shaft length reduces the first-order natural frequency of the prestressed rotor components. The structure also experiences stress stiffening, which is more obvious in the high-order modes. The natural frequency of the rotor in the wet mode is about 16% less than that in the dry mode for the various shaft lengths due to the added mass of the water on the surface which reduces the natural frequency. In the wet modal analysis, when the structure is in a different fluid medium, the influence of its modal distribution will also change, this is because the additional mass produced by the fluid medium of different density on the structure surface is different. Thus, the wet modal analysis of the rotor is important for more accurate dynamic analyses.